Determination of Sustainable Factory Locations for the Lemon Agroindustry using AHP, Mapping and Water Management - Prawiranegara, Boy Macklin Pareira; Asdak, Chay; Octoyne, Aisyah; Kendarto, Dwi Rustan (PERTETA, 2024)
This research was conducted in Suntenjaya Village, Lembang, West Bandung Regency, focusing on lemon agro-industry development through the Analytical Hierarchy Process (AHP) method approach, area mapping, and water management to determine a sustainable factory location. The main objective is the selection of factory site by integrating lemon production considering sustainable agriculture aspects, product aspects, and water conservation programs. The results of the study provide a strong foundation for sustainable agro-industrial development will support sustainable agriculture, local economy, and environmental protection. The research also combined qualitative and quantitative elements with a mixed approach that included Focus Group Discussion (FGD) and AHP with the results showing that integrated drainage management was the top priority, followed by sanitation, clean water, reforestation, and sustainable agriculture. Mapping of areas based on geographical characteristics such as rainfall, slope, and soil type provided a map of water infiltration rates that became a key guide in planning water conservation programs. This research has positive implications in supporting sustainable agricultural practices and local economic empowerment. The results of the AHP analysis and area mapping form a strong framework for the development of a sustainable lemon agro-industry with positive economic and environmental impacts.